RBM25 Mediates Abiotic Responses in Plants - Cheng, Chunhong; Wang, Zhijuan; Yuan, Bingjian; Li, Xia (Frontiers in Plant Science, 2017)
Alternative splicing (AS) of pre-mRNAs is one of the most important post-transcriptional regulations that enable a single gene to code for multiple proteins resulting in the biodiversity of proteins in eukaryotes. Recently, we have shown that an Arabidopsis thaliana RNA recognition motif (RRM)-containing protein RBM25 is a novel splicing factor to modulate plant response to ABA during seed germination and post-germination through regulating HAB1 pre-mRNA AS. Here we show that RBM25 is preferentially expressed in stomata and vascular tissues in Arabidopsis and is induced by ABA and abiotic stresses. Loss-of-function mutant is highly tolerant to drought and sensitive to salt stress. Bioinformatic analysis and expression assays reveal that Arabidopsis RBM25 is induced by multiple abiotic stresses, suggesting a crucial role of RBM25 in Arabidopsis responses to adverse environmental conditions. Furthermore, we provide a comprehensive characterization of the homologous genes of Arabidopsis RBM25 based on the latest plant genome sequences and public microarray databases. Fourteen homologous genes are identified in different plant species which show similar structure in gene and protein. Notably, the promoter analysis reveals that RBM25 homologs are likely controlled by the regulators involved in multiple plant growth and abiotic stresses, such as drought and unfavorable temperature. The comparative analysis of general and unique cis regulatory elements of the RBM25 homologs highlights the conserved and unique molecular processes that modulate plant response to abiotic stresses through RBM25-mediated alternative splicing.